The Effect of Isotonic Drinks and Yellow Watermelon Juice on the Hydration Status of T-Rex Jawa’s Football and Futsal Players - Ivadha, Bernica Irnandianis (Sport and Nutrition Journal, 2023)
Hydration status is a condition that describes the balance of fluids in the body and is an important condition for ensuring the metabolic function of body cells. The purpose of this study was to determine the effect of giving iosotonic drinks and yellow watermelon juice on the hydration status of T-Rex Jawa’s football and futsal players. This research is a quasi-experimental study using crossover design. The sample was 26 people, all of whom were used as control groups and treatment groups. The control group was given 350 ml of isotonic drink and the treatment group was given 350 ml of yellow watermelon juice. Measurements in this study included weight, height, physical activity, energy intake, nutrients and fluids and hydration status values. The results showed that there were differences in hydration status values before and after treatment in both the control group and the treatment group. The Mann Whitney test showed p=0.006, namely that there was a significant difference between the decrease in the hydration status value of the control group and the treatment group, where a greater decrease was shown by the control group. Nutritional status, physical activity, energy intake, macronutrients, minerals and fluids are not correlated with hydration status.